Xenon solubility and formation of supercritical xenon precipitates in glasses under non-equilibrium conditions. Issue 1 (December 2018) - Mir, Anamul; Hinks, J.; Delaye, Jean-Marc; Peuget, Sylvain; Donnelly, S.
Abstract Estimates of noble gas solubility in glasses and minerals are important to understand the origin of these gases, particularly xenon, in the atmosphere. However, technical difficulties and ambiguities in quantifying the dissolved gases introduce large uncertainties in the solubility estimates. We present here the use of transmission electron microscopy (TEM) within-situ noble gas ion implantation as a non-equilibrium approach for noble gas solubility estimates. Using a suitable Xe equation of state and Monte-Carlo simulations of TEM images, a clear distinction between Xe filled precipitates and empty voids is made. Furthermore, implantation-induced changes in the solubility are estimated using molecular dynamics simulations. These studies allow us to evaluate the xenon solubility of irradiated and pristine silica glasses and monitorin-situ the diffusion-mediated dynamics between the precipitates and voids — otherwise impossible to capture. On exceeding the solubility limit, supercritical xenon precipitates, stable at least up to 1155 K, are formed. The results highlight the high capacity of silicates to store xenon and, predict higher solubility of radiogenic xenon due to the accompanying radiation damage.